Karakterisasi α-Amilase dari Aspergillus versicolor 3a1 yang Diproduksi pada Media Limbah Cair Tapioka - Fitratul Aini; Nisa Rachmania Mubarik; Lisdar A. Manaf (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2009)
The aim of this experiment was to characterize A. versicolor 3a1 α-amylase produced on cassava liquid waste media. Two types of media, base and combination media, were used as a comparison. Cassava liquid waste media contains 1% cassava starch, 1% yeast extract, 0.13% KH2PO4, and 0.05% MgSO4 diluted in cassava liquid waste. Base media contains same composition but using aquadest as a solvent, and combination media using mixture of aquadest and cassava liquid waste. A. versicolor 3a1 α-amylase showed its maximum specific activity in cassava liquid waste, base, and combination media after 3, 7, and 4 days incubation, respectively. Crude extract of α-amylase fromA. versicolor 3a1 was precipitated in 20-80% (w/v) ammonium sulphate. Precipitation of A. versicolor 3a1 α-amylase with 70% (w/v) ammonium sulphate on cassava liquidwaste, 60% on base media, and 60% on combination media will increase its specific activity 16.6, 4.28, and 5.65 times, respectively, compared to the specific activities ofcrude before precipitation. α-Amylase crude extract from A. versicolor 3a1 from all media showed its highest specific activity at 70oC and pH 5.0, and addition of FeSO4 increased the specific activity. Precipitated A. versicolor 3a1 α-amylase from all media showed its highest specific activity at 70oC and pH 6.0. Addition of FeSO4 precipitated 3a1 α-amylase from base and combination media will increase its specific activity, while MgSO4 will increase its specific activity in cassava liquid waste media. Thermostability assay revealed that the crude and the precipitated 3a1 α-amylase were relatively stable at 70oC up to 180 minutes incubation, except for precipitated3a1 -amylase on cassava waste media. Crude α-amylase 3a1 was relatively stable at pH 5-9 up to 1 hour incubation with wide pH ranges, while the precipitated with narrow pH ranges.